Extended-spectrum beta-lactamases among Klebsiella pneumoniae from Iraqi patients with community-acquired pneumonia - Raouf,Faez Erees Abdul (2022)
SUMMARY OBJECTIVE: Beta-lactams resistance is a major clinical problem in treating pneumonia. This study aimed to detect the extended-spectrum beta-lactamases (ESBL) genes in Klebsiella pneumoniae among patients with community-acquired pneumonia (CAP) in Al-Najaf City, Iraq. METHODS: A total of 511 sputum samples were obtained from all suspected patients with CAP in Al-Najaf City, Iraq, from March 2020 to September 2020. Sputum samples were subjected to microbiological tests. The disk diffusion method was used to test antibiotic sensitivity. Production of ESBLs was identified using phenotypic and genotypic methods. RESULTS: The total prevalence of K. pneumoniae was 31.9% (163/511). Using CHROM agar, 41 (25.2%) isolates were ESBL producers. The imipenem 0.0% (n=0/41) and norfloxacin 0.0% (n=0/41) were the most effective antibiotics. The multiplex polymerase chain reaction showed that 46.3% (n=19/41) of isolates harbored ESBL genes. Out of 19 ESBL producers, 47.4% and 15.8% harbored blaCTX-M and blaSHV, respectively. While blaCTX-M and blaSHV genes were detected in 7 (36.8%) isolates, simultaneously. CONCLUSIONS: The imipenem and norfloxacin can be used in empirical treatment of K. pneumoniae isolates in Iraq. The emergence of K. pneumoniae strains harboring ESBL resistance genes necessitates the development of a regular surveillance program to prevent the spreading of these isolates more in Iraqi health care systems.